Proceedings of the 2nd Annual International Conference on Mobile Computing and Networking 1996
DOI: 10.1145/236387.236388
|View full text |Cite
|
Sign up to set email alerts
|

Low-loss TCP/IP header compression for wireless networks

Abstract: Wireless is becoming a popular way to connect mobile computers to the Internet and other networks. The bandwidth of wireless links will probably always be limited due to properties of the physical medium and regulatory limits on the use of frequencies for radio communication. Therefore, it is necessary for network protocols to utilize the available bandwidth e ciently. Headers of IP packets are growing and the bandwidth required for transmitting headers is increasing. With the coming of IPv6 the address size i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(45 citation statements)
references
References 10 publications
(3 reference statements)
0
43
0
Order By: Relevance
“…In [6] a header compression scheme that provided robustness at the expense of reduced compression was introduced and further optimized in [7,8]. On the other hand, in [9] a number of extensions to the seminal scheme [3] were proposed; these extensions provide support for UDP, IPv6, and additional TCP features and incorporate further refined compression mechanisms [10]; a performance evaluation for packet voice over the wired internet is reported in [11]. We also note that a header compression scheme specifically for IPv6 based communication with mobile wireless clients has been developed [12].…”
Section: Related Workmentioning
confidence: 99%
“…In [6] a header compression scheme that provided robustness at the expense of reduced compression was introduced and further optimized in [7,8]. On the other hand, in [9] a number of extensions to the seminal scheme [3] were proposed; these extensions provide support for UDP, IPv6, and additional TCP features and incorporate further refined compression mechanisms [10]; a performance evaluation for packet voice over the wired internet is reported in [11]. We also note that a header compression scheme specifically for IPv6 based communication with mobile wireless clients has been developed [12].…”
Section: Related Workmentioning
confidence: 99%
“…Degermark et al [9] observed that the statistics of the compressed headers are not random, but that some residual redundancy remains in them. Often times, the compressed headers are the same from one packet to the next.…”
Section: Header Compression Methodologymentioning
confidence: 99%
“…Most of the attention was given to the overhead of Transmission Control Protocol (TCP), User Datagram Protocol (UDP), and IP in ad hoc networks [3,4]. What is most striking about all the approaches to date is the continued assumption of a layered-protocol architecture based on in-band, in-packet signaling in which one layer encapsulates the higher layer, and all protocol headers are included in each packet.…”
Section: Improving the Transition To A Wireless Mediummentioning
confidence: 99%